2004
DOI: 10.1021/ie030428h
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Transfer Characteristics of Surface Aerators and Gas-Inducing Impellers

Abstract: Liquid-side mass-transfer coefficients (k L a) were measured in surface aerators and self-inducingtype reactors. The measurements were made in 1.0-and 1.5-m-i.d. cylindrical and 8.2 × 8.2-m square tanks using physical absorption of oxygen. The effect of liquid submergence was investigated in detail. Further, the effects of the diameter of the tank, the ratio of the impeller diameter to the tank diameter, and the clearance of the impeller from the tank bottom were also studied. Three different impeller designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…Generally impeller position has been fixed at 1/6 to 1/2 of tank diameter [6]. Patil et al [11] has conformed the observations reported by Backhurst et al [13]. Takase et al [12] has reported different effects of impeller clearance.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Generally impeller position has been fixed at 1/6 to 1/2 of tank diameter [6]. Patil et al [11] has conformed the observations reported by Backhurst et al [13]. Takase et al [12] has reported different effects of impeller clearance.…”
Section: Introductionmentioning
confidence: 72%
“…Montante et al [9] investigated the effect of the impeller clearance on the flow and turbulence fields in a fully baffled vessel stirred by a Rushton turbine. The performance of surface aerators is * Corresponding author, Email:bimk@iitg.ernet.in known to depend on the impeller submergence, which indicates the position of rotor in stirred [11]. The performance of surface aerators is * Corresponding author, Email:bimk@iitg.ernet.in known to depend on the impeller submergence, which indicates the position of rotor in stirred [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been utilized to determine power consumption (Ascanio et al, 2004): strain gauges and telemetry (Karcz and Major, 1998;Moucha et al, 2003;Fentiman et al, 1998), load cell setup associated with a torque table with a controlled traversing mechanism (Patil et al, 2004;Kumaresan and Joshi, 2006;Kumaresan et al, 2005), calorimeter (Oosterhuis and Kossen, 1981;Bourne et al, 1981), torquemeter (Pinho et al, 1997;Ravelet et al, 2007;Vasconcelos et al, 1999), and dynamometer (Wang et al, 2009;Zhao et al, 2011).…”
Section: Power Consumptionmentioning
confidence: 99%
“…In these cases achieving high aeration or oxygen mass transfer ( ) is not the last target, but the minimization of power consumption is very important [7], [8].…”
Section: Introductionmentioning
confidence: 99%